Electrostatic manipulation of piezoelectric fibres using a sharp probe electrode in a dielectric liquid: Analysis of the electrohydrodynamic phenomena - Capria, Ennio (Cranfield University, 2007)
Micro-assembly techniques have been identified as a major technology ‘pillar’ that will underpin further advancements in integrated micro-and nano-systems. In practice, there is a generic requirement for component parts that are often fragile, or that have been prepared by mutually incompatible processes, to be brought together to make a complete working system. This thesis discusses an electrostatic positioning technique for micro-scale elements that could form the basis of an industrial process. A highly non-uniform field generated between a needle-like upper electrode and a bottom flat electrode can be used to electrostatically capture, displace, and relocate elements into a predefined spatial configuration. The very intense field at the needle tip can facilitate the collection of the material at a precise point. However charge injection and local dielectric breakdown must also be considered as they can induce instability near the tip, and consequently interfere with any picking up action. The principal physical phenomena and potential benefits are analysed and discussed, considering three different configurations to achieve the pick and place operation for a micro-fibre in the needle-plane configuration. The first two are operated on an isolated single fibre lying on a flat bottom electrode, applying respectively a DC or an AC voltage. The third case is that of a group of fibres, and it exploits a dielectrophoretic chain structuring effect to assist in the micro-manipulation technique. Experimentation has focussed on the importance of the charge transfer mechanisms, leading to a model which provides good agreement with the observed behaviour. Moreover, an analysis of the forces exerted on the fibres showed that they arise not only from a polarisation effect, but that there is also an electrophoretic contribution. The viability of the proposed technique has been demonstrated using lead zirconate titanate (PZT rods and carbon fibres).